A lattice-mechanical metamaterial with tunable two-step deformation, tunable stiffness, tunable energy absorption and programmable properties - Chenyang Liu; Zexin Gao; Jiahui Chang; Jianan Zhao; Song Qiu; Peiran Yu; Xi Zhang (Materials Research Express)
Mechanical metamaterials have attracted much attention in recent years because of excellent properties. However, most mechanical metamaterials have only a relatively fixed and single deformation mode. Although some multi-step deformation metamaterials have been proposed, their rich static and dynamic mechanical properties have yet to be studied in depth. Therefore, a lattice-mechanical metamaterial is introduced in this study. Under vertical compression, different unit cells under the same architecture can achieve two or three steps of deformation, respectively. Metamaterials built from these unit cells can also achieve the same properties. These properties can exist in multiple directions and are not affected by the number of unit cells. In addition, this metamaterial not only has adjustable two-step deformation, adjustable stiffness, and adjustable energy absorption properties but it can also be spatially programmed by changing geometric parameters and tessellation. Finally, a 3D design version of the metamaterial is provided, and its conceptual application is briefly demonstrated. The developed metamaterial can achieve more static and dynamic mechanical properties while taking into account two-step deformation. This can provide richer content for the development of mechanical metamaterials and also provide new perspectives for the application of energy absorbers, aerospace, and industrial products.